Price effects of economic and production factors across weights of feeder steers and heifers in southern Great Plains states - Lister, Garrett Craig (Kansas State University, 2014)
Feeder cattle are placed into feedlots at varying weights. This placement weight is the result of procurement decisions by cattle feeders and of marketing decisions by cow/calf and stocker/backgrounder producers. Increased understanding of the behavior of these markets can help both buyers and sellers of feeder cattle make these decisions. Past research has used linear or quadratic variables or interaction variables in order to model the effects of weight on price. This study instead divides the market for feeder cattle into ten distinct subsets which are evaluated independently. The feeder cattle market for four major cattle feeding states in the Southern Great Plains (Nebraska, Kansas, Oklahoma and Texas) was divided into ten subsets, five in each gender. Each of these represent feeder cattle coming to market in a 50 pound weight range, centered upon 525, 625, 725, 825 and 925 pounds. Each of these subsets was analyzed using seven independent variables selected based upon previous research and economic rationale. These variables were the live futures price, previous feedlot returns, feeder cattle inventory, interest rate, feedlot capacity utilization, cost of gain and pasture conditions. The data for these variables were collected from public sources, aggregated into monthly observations and differenced to correct for nonstationarity. Analysis was conducted using ordinary least squares regressions. Results are reported and trends between weight classes discussed along with their implications. Findings support that feeder cattle of different weights are not perfect substitutes and that market and production factors do not influence all weights of feeder cattle the same. In fact, factors which positively and negatively affect feeder cattle price seem to signal that demand for, or in the case of pasture supply of, feeder cattle of a particular weight has changed and that placement price-weight relationships will adjust accordingly.
Keywords: Feeder cattle; Price analysis; Price-weight relationships; Economics, Agricultural (0503)